Using web-based training to enhance perceptual-cognitive skills in complex dynamic offside events. Issue 2 (17th January 2016) - Put, Koen; Wagemans, Johan; Spitz, Jochim; Williams, A. Mark; Helsen, Werner F.
Abstract: In association football, the difficulty in making offside decisions depends on both perceptual and cognitive processes. Therefore, the objectives of the present study were to enhance the decision-making skills of assistant referees by further developing their ability to (1) time slice the incoming information flow into series of isolated time frames during an ongoing offside situation and (2) use this information to mentally read off the spatial positions of the key-role players. Training ( n = 10) and control groups ( n = 10) were exposed to a pre- and post-test, consisting of an offside decision-making and frame recognition test. In the latter, assistant referees were asked to indicate which of five photos best represented the spatial position of the defender and attacker at the moment of the pass. Only the training group received 12 web-based offside training sessions. First, the training group improved in mentally freezing, holding and scanning the mental picture of the offside situation in short-term memory from pre- to post-test, as evidenced by an increased recognition accuracy. Second, the improvement in recognition accuracy resulted in enhanced performance on the offside decision-making task. The benefits of web-based training are highlighted.